Sons, corpos e lugares: para uma metonímia das cidades musicais contemporâneas - Guerra, Paula (2021)
The present article intends to demonstrate that musical cities have been undergoing metamorphosis. These are composed of other spaces, bodies and movements that also mark their sonorities. This essay focuses on the perception of voguing as an essential element in the creation and demarcation of contemporary music cities in the Global South. From its historical contextualisation, the article focuses on an explanatory example of this dimension. Of the body as a stage of resistance, but also as the materialisation of multiple processes of social exclusion. Further, we understand voguing and the body as forms and modes of existence, within a patriarchal society deeply oppressive of LGBTQI+ communities. To this end, as we focus on the body as a performative matrix of urban, relational and social spaces, we hold up a set of photographs that demonstrate these affirmations, all of them referring to the House of Império, a house - in its historical conception - with connections to Rio de Janeiro, São Paulo and Minas Gerais. We intend, thus, to show another side of contemporary music cities.